The Effect of Prior Police Contact on Victimization Reporting: Results From the Police-Public Contact and National Crime Victimization Surveys, United States, 2002-2011 - Slocum, Lee Ann ([Verlag nicht ermittelbar], 2021)
This study examines whether or not prior experiences with the police, both directly and indirectly through the experiences of others, can influence one's decision to report a crime. Data from the National Crime Victimization Survey (NCVS) was linked with the Police-Public Contact Survey (PPCS) to construct a dataset of the police-related experiences of crime victims and non-victims. Variables include information on the prevalence, frequency, and the nature of respondents' encounters with the police in the prior year, as well as respondents' personal and household victimization experiences that occurred after the administration of the PPCS, including whether the crime was reported to the police. Demographic variables include age, race, gender, education, and socioeconomic status. The ICPSR's holdings for both the NCVS and the PPCS are available in the NCVS series.